A cytochrome P450 allele confers pyrethroid resistance on a major African malaria vector, reducing insecticide-treated bednet efficacy - Weedall, G.D.; Mugenzi, L.M.; Menze, B.D.; Tchouakui, M.; Ibrahim, S.S.; Amvongo-Adjia, N.; Irving, H.; Wondji, M.J.; Tchoupo, M.; Djouaka, R.; Riveron, J.M.; Wondji, C.S. (American Association for the Advancement of Science, 2019)
Metabolic resistance to insecticides such as pyrethroids in mosquito vectors threatens control of malaria in Africa. Unless it is managed, recent gains in reducing malaria transmission could be lost. To improve monitoring and assess the impact of insecticide resistance on malaria control interventions, we elucidated the molecular basis of pyrethroid resistance in the major African malaria vector, Anopheles funestus. We showed that a single cytochrome P450 allele (CYP6P9a_R) in A. funestus reduced the efficacy of insecticide-treated bednets for preventing transmission of malaria in southern Africa. Expression of key insecticide resistance genes was detected in populations of this mosquito vector throughout Africa but varied according to the region. Signatures of selection and adaptive evolutionary traits including structural polymorphisms and cis-regulatory transcription factor binding sites were detected with evidence of selection due to the scale-up of insecticide-treated bednet use. A cis-regulatory polymorphism driving the overexpression of the major resistance gene CYP6P9a allowed us to design a DNA-based assay for cytochrome P450–mediated resistance to pyrethroid insecticides. Using this assay, we tracked the spread of pyrethroid resistance and found that it was almost fixed in mosquitoes from southern Africa but was absent from mosquitoes collected elsewhere in Africa. Furthermore, a field study in experimental huts in Cameroon demonstrated that mosquitoes carrying the resistance CYP6P9a_R allele survived and succeeded in blood feeding more often than did mosquitoes that lacked this allele. Our findings highlight the need to introduce a new generation of insecticide-treated bednets for malaria control that do not rely on pyrethroid insecticides.